Pengaruh Emotional Intelligence, Work-Family Conflict, dan Non-Work Presenteeism Terhadap Job Performance Guru di SMP – SMA Dian Harapan Daan Mogot Jakarta - sertauli, maria (Universitas Muhammadiyah Surakarta, 2024)
Education is vital in life. Educators must excel in their roles as leaders in formal education and perform well in their jobs. Any issues arising from these aspects will affect the assessment of a teacher's job performance in a school. This research aims to examine the influence of emotional intelligence, work-family conflict, and non-work presenteeism on teacher job performance at SMP-SMA Dian Harapan, Daan Mogot Jakarta. A questionnaire was distributed to gather data from 73 teachers. This study is quantitative research using path analysis as the analytical method. The results indicate that emotional intelligence has a positive influence (0,390) on job performance, while work-family conflict and non-work presenteeism have a negative influence (-0,030 and -0,293) on job performance.